Cooperative interaction between organic and inorganic moieties in hybrid silica nanohelices for enantioselective interaction. Issue 97 (17th November 2022) - Nag, Rahul; Okazaki, Yutaka; Scalabre, Antoine; Anfar, Zakaria; Nlate, Sylvain; Buffeteau, Thierry; Oda, Reiko; Pouget, Emilie
Abstract : Hybrid nanometric helical structures formed by the molecular assemblies of dicationic gemini surfactants with tartrate counterions covered with helical silica walls interact differently with matching or mismatching enantiomers of the tartrate. Abstract : Hybrid nanometric helical structures formed by the molecular assemblies of dicationic gemini surfactants with tartrate counterions covered with helical silica walls interact differently with matching or mismatching enantiomers of the tartrate. The difference of the interaction is based on the cooperativity between the chiral crystalline gemini surfactant molecular organization/conformation and the rigid chiral nanospace formed by the helical silica wall.